PENGARUH GAYA KEPEMIPINAN DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PT OCEAN CENTRA FURNINDO MEDAN - Derimasari, Arytata; Purba, Purnama Yanti; Andi, Andi; Seronica, Seronica; Susanto, William (Aksara Public, 2019)
This study aims to examine and analyze the influence of leadership style and physical work environment on work performance in PT Ocean Centra Furnindo Medan. The phenomenon of conducting leadership style to the company tends to be less good, which can be seen from the rare leadership present to the company to attend meetings and provide problem solving to employees, the work environment less comfortable to carry out work, and work performance that tends to decrease can be seen from the decline in the number of sales at PT Ocean Centra Furnindo. The sampling technique used is simple random sampling with a total sample of 97 employees. The method used is a quantitative approach with a type of quantitative descriptive research and the nature of research is descriptive explanatory. The data analysis method used is multiple linear regression. The results of showed with significant level 0,05 that the leadership style has a positive and significant effect on the work performance partially with Tcount > Ttable (5,167 > 1.985) and physical work environment has a positive and significant effect on the work performance partially with Tcount > Ttable (2,444 > 1.985). Leadership style and physical work environment have a positive and significant effect on work performance simultaneously with Fcount > Ftable (16,747 > 3,090).